A prognostic index for patients within the intermediate stage of hepatocellular carcinoma. Issue 5 (May 2016) - Di Costanzo, Giovan Giuseppe; Signoriello, Simona; Tortora, Raffaella; Gallo, Ciro
Abstract : Objective: The Barcelona Clinic Liver Cancer algorithm is the most widely used staging system for hepatocellular carcinoma, but the intermediate stage of this classification comprises a very heterogeneous group of patients with different survival probabilities. The aim of our study was to construct a simple prognostic index for identifying subgroups of patients with different prognoses within the intermediate stage. Patients and methods: Three-hundred and seven patients were retrospectively analyzed and randomly divided into a training sample ( n =205), from which the model was developed, and a test sample ( n =102), to independently assess the model's performance. Results: Four variables were retained in the final multivariate model: hepatic failure, number of nodules, α-fetoprotein, and albumin, with hazard ratios equal to 2.22 (95% confidence interval: 1.52–3.24), 1.47 (1.00–2.18), 2.34 (1.56–3.52), and 1.75 (1.26–2.44), respectively. The score system was derived by summing up the linear weights assigned to the four covariates according to the observed regression coefficients. The score ranged between 4 and 13; to avoid sparse-data bias arising from small numbers within strata, only four categories (4–5, 6–7, 8–9, 10–13) were identified. The prognosis worsened significantly with increasing score and the C -index for discriminatory accuracy was equal to 0.66 (95% confidence interval: 0.60–0.72). The score was validated in the test sample (log-rank test P =0.02). Similar results were found when evaluating the score as a continuous variable. Conclusion: The simple prognostic index predicts survival in patients with intermediate-stage hepatocellular carcinoma. This score might help guide treatment selection and patient stratification in clinical studies. Abstract : Supplemental Digital Content is available in the text.